2010
DOI: 10.1007/s00425-010-1254-2
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of an FT-homologous gene of apple induces early flowering in annual and perennial plants

Abstract: The protein encoded by the FLOWERING LOCUS T (FT) gene from Arabidopsis thaliana seems to be the long-searched florigen, and over-expression of FT orthologues resulted in accelerated flower development in annual and perennial plants. In the present study, we isolated two allelic mRNA sequences of an FT-homologous gene from apple, which was designated as MdFT1. Using a SSR motif this gene was mapped on LG 12 of apple. Over-expression of MdFT1 in Arabidopsis and the commercially important tree species poplar and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(85 citation statements)
references
References 58 publications
3
82
0
Order By: Relevance
“…Abnormality in the number of floral parts of MdFToverexpressing transgenic apples has been reported previously (Kotoda et al 2010;Tränkner et al 2010;Yamagishi et al 2011). This finding indicated that FT overexpression was able to cause early flowering in apple, but was unable to maintain the induction of floral organ development.…”
Section: Characterization Of Psmrolc::atft Transgenic Applementioning
confidence: 55%
See 1 more Smart Citation
“…Abnormality in the number of floral parts of MdFToverexpressing transgenic apples has been reported previously (Kotoda et al 2010;Tränkner et al 2010;Yamagishi et al 2011). This finding indicated that FT overexpression was able to cause early flowering in apple, but was unable to maintain the induction of floral organ development.…”
Section: Characterization Of Psmrolc::atft Transgenic Applementioning
confidence: 55%
“…The two genes are expressed mainly in floral tissues and at different stages of flower development, which suggests that the two genes play different roles in the onset and maturation of apple flowers (Kotoda et al 2010). Transgenic apple plants that express 35S::MdFT1 show early flowering and promotion of flower development within a year after transformation (Kotoda et al 2010;Tränkner et al 2010). Similarly strong promotion of flowering by FT overexpression has been reported for the woody plants poplar, citrus, pear and plum (Endo et al 2005;Hsu et al 2006;Matsuda et al 2009;Srinivasan et al 2012).…”
mentioning
confidence: 80%
“…BpMADS4 transgenic lines are currently being used for apple breeding (Flachowsky et al 2011). The apple gene MdFT2, homologous of FT gene, promoted early flowering in apple and poplar (Tränkner et al 2010). Arabidopsis flowering time genes Leafy (Schultz & Haughn 1991) and Flowering locus T (Blázquez & Weigel 1999) allow the hitherto most efficient early flowering induction in poplar (Weigel & Nilsson 1995, Rottmann et al 2000, Zhang et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis flowering time genes Leafy (Schultz & Haughn 1991) and Flowering locus T (Blázquez & Weigel 1999) allow the hitherto most efficient early flowering induction in poplar (Weigel & Nilsson 1995, Rottmann et al 2000, Zhang et al 2010. Furthermore, it has been shown that transgenes can induce early flowering in trees more efficiently than cisgenes (Rottmann et al 2000, Zhang et al 2010, Flachowsky et al 2011, Tränkner et al 2010. Possibly, transgenes are less prone to "endogenous repressors" than cisgenes (Rottmann et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…5c). Because FT protein may not be a mobile signal in apple (Tränkner et al, 2010), MdFT1 expression was shown in flower buds. MdFT1 expression increased in mid-July, suggesting that flowering induction and initiation occur between late June and mid-July, as described by Kotoda et al (2010).…”
Section: Mdmads11 Gene Expression In Buds and Floral Organsmentioning
confidence: 99%